Minat Investasi di Kalangan Mahasiswa Generasi Milenial di Surakarta - Tri Ratna Pamikatsih; Ari Susanti (JURNAL ILMIAH EDUNOMIKA, 2021)
This research aims to see how the influence of capital market knowledge and returns on student investment interest. This research was conducted using quantitative methods with sample size of 120 respondents. The analysis used is multiple linear regression analysis. The results of this research indicated that capital knowledge has a significant effect on student investment interest, When student understand about capital market knowledge deeply, it willl increase the student interest on invetsment. Return also also has a significant effect on student investment interest. The level of profit offered by the capital market is the basis for student interest in investing